Olfactory preferences of gravid femaile stable flies Stomoxys calcitrans L. (Diptera : muscidae) and their fitness consequences - Weldon, Christopher W. (University of Pretoria, 2019)
Thesis (PhD)--University of Pretoria, 2019.